The Law Relating To Compulsory Third Party Motor Insurance In Malaysia - Mahmood, Nik Ramlah (Journal of Malaysian and Comparative Law, 1990)
The tort of negligence allows the victim of road accident to sue the tortfeasor for damages. However, even if negligence is established and an award of damages is made, whether the victim will be able to enforce the judgment depends upon the financial ability of the tortfeasor. If the tortfeasor happens to be a man of straw who is uninsured against such risks, the victim will not in fact get the damages awarded.